2022
DOI: 10.3389/fnut.2022.977278
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of postprandial glycemic response patterns to white rice and glucose in healthy adults: Identifying subgroups by clustering analysis

Abstract: ObjectivesLarge interpersonal variability in postprandial glycemic response (PGR) to white rice has been reported, and differences in the PGR patterns during the oral glucose tolerance test (OGTT) have been documented. However, there is scant study on the PGR patterns of white rice. We examined the typical PGR patterns of white rice and glucose and the association between them.Materials and methodsWe analyzed the data of 3-h PGRs to white rice (WR) and glucose (G) of 114 normoglycemic female subjects of simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Portugal is the second country in the European Union with the highest prevalence of diabetes (13.6% of the population aged between 20 and 79) [32]. Several nutritional studies have shown that the excessive consumption of white rice is associated with an increased risk of non-communicable diseases, namely diabetes, hypertension, obesity, and cardiovascular diseases [33][34][35][36][37][38][39]. Many studies have discussed GI and its importance in controlling diabetes and related diseases and demonstrated the importance of a food-centred approach [29,[40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Portugal is the second country in the European Union with the highest prevalence of diabetes (13.6% of the population aged between 20 and 79) [32]. Several nutritional studies have shown that the excessive consumption of white rice is associated with an increased risk of non-communicable diseases, namely diabetes, hypertension, obesity, and cardiovascular diseases [33][34][35][36][37][38][39]. Many studies have discussed GI and its importance in controlling diabetes and related diseases and demonstrated the importance of a food-centred approach [29,[40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%